2015
DOI: 10.1007/s11135-015-0294-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of energy consumption and urbanization on environmental pollution in South Asian countries: a nonparametric panel approach

Abstract: This paper investigates the relationship between environmental pollution, energy consumption, and the level of urbanization in South Asian countries over the period 1978-2011. The sample is a panel of three selected countries, namely, India, Pakistan, and Bangladesh. The relationship is investigated by employing nonparametric additive model with country and time specific fixed effects. The findings suggest that the relationship between carbon dioxide emissions and energy consumption is nonlinear in nature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 29 publications
3
19
1
Order By: Relevance
“…Al-Mulali et al (2015) studied the cointegration among carbon dioxide emission, economic growth, urbanization, financial development and renewable electricity production using data of twenty-three European economies for the period 1990 to 2013, and it was concluded that urbanization, growth and financial development contributed to carbon emissions (Al-Mulali et al 2015). Irfan and Shaw (2017) considered that there existed an inverted U-shaped relation of CO2 emissions with urbanization. Particularly, a threshold effect was found to exist between urbanization and carbon emissions and that these emissions could be repressed once the level of urbanization exceeded that threshold (Irfan and Shaw, 2017).…”
Section: Urbanization and The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Mulali et al (2015) studied the cointegration among carbon dioxide emission, economic growth, urbanization, financial development and renewable electricity production using data of twenty-three European economies for the period 1990 to 2013, and it was concluded that urbanization, growth and financial development contributed to carbon emissions (Al-Mulali et al 2015). Irfan and Shaw (2017) considered that there existed an inverted U-shaped relation of CO2 emissions with urbanization. Particularly, a threshold effect was found to exist between urbanization and carbon emissions and that these emissions could be repressed once the level of urbanization exceeded that threshold (Irfan and Shaw, 2017).…”
Section: Urbanization and The Environmentmentioning
confidence: 99%
“…Irfan and Shaw (2017) considered that there existed an inverted U-shaped relation of CO2 emissions with urbanization. Particularly, a threshold effect was found to exist between urbanization and carbon emissions and that these emissions could be repressed once the level of urbanization exceeded that threshold (Irfan and Shaw, 2017).…”
Section: Urbanization and The Environmentmentioning
confidence: 99%
“…This is based on greater financial development that can increase output and economic growth. Recent empirical works have employed expanded production theory to simulate the association amongst financial development, consumption of energy and carbon dioxide emissions (CO 2 ) [28][29][30][31]. However, the use of emissions from the agricultural sector makes the study very different from the available literature.…”
Section: Materials and Econometric Methodsmentioning
confidence: 99%
“…Second, this method can be employed even if the selected study variables are stationary at I(0), I(1) or a combination of both. Third, the ARDL modelling approach has been found much more efficient when dealing with a small sample size [29]. The ARDL-bound test cointegrations equations are given by:…”
Section: Estimation Techniquementioning
confidence: 99%
“…In order to overcome this problem, Dietz and Rosat [23] STIRPAT model rewrote by. The general form of STIRPAT model can be specified as follows:…”
Section: Theoretical Model-extended Stirpatmentioning
confidence: 99%